Reviewing Laubscher’s empirical method to estimate subsidence limits - Contreras, C.; Elmo, D.; Jakubec, J.; Thomas, A. (Caving 2022: Proceedings of the Fifth International Conference on Block and Sublevel Caving, 2022)
The increasing global demand for mineral resources and the depletion of significant high-grade near-surface deposits is driving mining companies to consider cave mining as the ideal method to exploit large low-grade deposits at depth. A key characteristic of cave mining is the formation of a significant surface subsidence crater, which may impact nearby infrastructures, as well as have important environmental impacts. The most used empirical method in cave mining for estimating subsidence damage limits is the Laubscher method (2000). The original dataset at the core of the Laubscher chart does not reflect the conditions of the modern caves (i.e. deeper orebodies, stronger rock masses and higher production rates). In addition, there is a need to review the definition of the cave material factor. This paper explains the limitations related to the method and evaluates new cases from recent cave mining operations for checking the validity of the empirical subsidence chart.